Static and dynamic high pressure mineral physics - Fei, Yingwei; Walter, Michael (Cambridge University Press, 2022)
High pressure mineral physics is a field that has shaped our understanding of deep planetary interiors and revealed new material phenomena occurring at extreme conditions. Comprised of sixteen chapters written by well-established experts, this book covers recent advances in static and dynamic compression techniques and enhanced diagnostic capabilities, including synchrotron X-ray and neutron diffraction, spectroscopic measurements, in situ X-ray diffraction under dynamic loading, and multigrain crystallography at megabar pressures. Applications range from measuring equations of state, elasticity, and deformation of materials at high pressure, to high pressure synthesis, thermochemistry of high pressure phases, and new molecular compounds and superconductivity under extreme conditions. This book also introduces experimental geochemistry in the laser-heated diamond-anvil cell enabled by the focused ion beam technique for sample recovery and quantitative chemical analysis at submicron scale. Each chapter ends with an insightful perspective of future directions, making it an invaluable source for graduate students and researchers.